Neurorehabilitation for an individual with bilateral thalamic stroke and preexisting visual impairment presenting with impaired use of sensory cues: a case report. (3rd October 2021) - Kelly, Christina; Meyer, Jen; Hanks, Valery; Barefield, Christy
ABSTRACT: Introduction : Impaired balance is one of the primary causes of functional limitations. Related to sensory deficits specifically, balance disorder in stroke may be caused by decreased central integration of sensory cues, including somatosensory, visual and vestibular input. Case Presentation : This case describes a 23-year-old male with bilateral thalamic stroke following surgical resection of a recurring optic nerve meningioma. He had a complex medical history and is legally blind. He presented to outpatient neurorehabilitation 5 months following his stroke. He demonstrated absent light touch sensation and absent proprioception and kinesthetic awareness in his upper extremities, lower extremities, and trunk. Secondary to absent proprioception and vision and significant impairments related to shunt malfunction, he required total assistance for all mobility at initial examination. Discussion : After 8 months of intensive rehabilitation, he demonstrated substantial improvements in all functional mobility and recovery of sensation. Rehabilitation included interventions such as electrical stimulation, fluidotherapy, repetitive task training, and most significantly, external augmented feedback. This feedback included sensory cues, auditory and tactile cues, and maximizing the use of vestibular input. This case demonstrates that neurorehabilitation can benefit patients with impaired use of sensory cues and central integration.